2017
DOI: 10.1038/cddis.2017.212
|View full text |Cite|
|
Sign up to set email alerts
|

Damage-induced neuronal endopeptidase (DINE) enhances axonal regeneration potential of retinal ganglion cells after optic nerve injury

Abstract: Damage-induced neuronal endopeptidase (DINE)/endothelin-converting enzyme-like 1 (ECEL1) is a membrane-bound metalloprotease that we identified as a nerve regeneration-associated molecule. The expression of DINE is upregulated in response to nerve injury in both the peripheral and central nervous systems, while its transcription is regulated by the activating transcription factor 3 (ATF3), a potent hub-transcription factor for nerve regeneration. Despite its unique hallmark of injury-induced upregulation, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…However, previous work suggested that Ecel1 deletion has tended to reduce RGCs but did not significantly affect the survival of injured RGCs in Ecel1 KO Tg mice. 19 One possible explanation is that the permanent deletion of Ecel1 in Ecel1 KO Tg mice might change the expression of other genes or signaling pathways to compensate for the loss of Ecel1. In the retina of Ecel1 KO Tg mice, no significant difference was seen in the number of RGCs or the axonal projections of the optic nerve to the superior colliculus and lateral geniculate nucleus.…”
Section: Differences In Rgc Loss Between Aav2-crispr/ Cas9-ecel1 and mentioning
confidence: 99%
See 4 more Smart Citations
“…However, previous work suggested that Ecel1 deletion has tended to reduce RGCs but did not significantly affect the survival of injured RGCs in Ecel1 KO Tg mice. 19 One possible explanation is that the permanent deletion of Ecel1 in Ecel1 KO Tg mice might change the expression of other genes or signaling pathways to compensate for the loss of Ecel1. In the retina of Ecel1 KO Tg mice, no significant difference was seen in the number of RGCs or the axonal projections of the optic nerve to the superior colliculus and lateral geniculate nucleus.…”
Section: Differences In Rgc Loss Between Aav2-crispr/ Cas9-ecel1 and mentioning
confidence: 99%
“…In the retina of Ecel1 KO Tg mice, no significant difference was seen in the number of RGCs or the axonal projections of the optic nerve to the superior colliculus and lateral geniculate nucleus. 19 However, Ecel1 is expressed in the embryonic neural retina. 9 Thus, the retinal network surrounding the RGCs might somehow be changed.…”
Section: Differences In Rgc Loss Between Aav2-crispr/ Cas9-ecel1 and mentioning
confidence: 99%
See 3 more Smart Citations